Comparison the Physical and Mechanical Properties of Composite Materials (Al /SiC and Al/ B4C) Produced by Powder Technology (Journal of Engineering, 2017)
In this investigation, metal matrix composites (MMCs) were manufactured by using powder technology. Aluminum 6061 is reinforced with two different ceramics particles (SiC and B4C) with different volume fractions as (3, 6, 9 and 12 wt. %). The most important applications of particulate reinforcement of aluminum matrix are: Pistons, Connecting rods etc. The specimens were prepared by using aluminum powder with 150 µm in particle size and SiC, B4C powder with 200 µm in particle size. The chosen powders were mixed by using planetary mixing setup at 250 rpm for 4hr.with zinc stearate as an activator material in steel ball milling. After mixing process the powders were compacted by hydraulic unidirectional press type (Leybold Harris No. 36110) at 250 Kg/cm2 according to (ASTM-D 618). Finally the green compacts were sintered at 500  for 3 hr. by using electrical furnace with argon atmosphere. There are many examinations and tests were done for the produced metal matrix composites (MMCS), (Al/ SiC and Al/B4C) such as examination of the microstructure, mechanical tests (hardness and compressive strength), physical tests (density test before and after sintering, also porosity test). The results of this investigation showed that improving the physical properties (theoretical density, experimental density, porosity) and mechanical properties (Rockwell hardness and compressive strength).